2009
DOI: 10.1007/s10144-009-0150-8
|View full text |Cite
|
Sign up to set email alerts
|

Distance decay of community dynamics in rocky intertidal sessile assemblages evaluated by transition matrix models

Abstract: It is well known that the similarity in species composition between two communities decays with the geographic distance that separates them. It is thus likely that the similarity in the dynamics of two communities also decays with distance, because the distance-decay relationship is fundamental in nature. However, the distancedecay relationships of community dynamics have not yet been revealed. We used transition matrix models to evaluate distance-decay relationships of seasonal community dynamics (from spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
1
8
1
Order By: Relevance
“…The structure of biofouling communities became less similar with increasing geographical distance between sampled mussel farms, making this study the first known, documented account of distance− decay in biofouling communities associated with artificial structures. The slope of the relationship between distance and community similarity in this study was similar to those recorded for intertidal sessile assemblages, but greater than those documented for marine fish communities (Oliva & Teresa 2005, Tsujino et al 2010). This contrast makes sense given that the rate of decline of similarity would be greater for organisms with a lower dispersal potential (e.g.…”
Section: Patterns Of Spatial Variation In Biofouling Communitiessupporting
confidence: 85%
See 1 more Smart Citation
“…The structure of biofouling communities became less similar with increasing geographical distance between sampled mussel farms, making this study the first known, documented account of distance− decay in biofouling communities associated with artificial structures. The slope of the relationship between distance and community similarity in this study was similar to those recorded for intertidal sessile assemblages, but greater than those documented for marine fish communities (Oliva & Teresa 2005, Tsujino et al 2010). This contrast makes sense given that the rate of decline of similarity would be greater for organisms with a lower dispersal potential (e.g.…”
Section: Patterns Of Spatial Variation In Biofouling Communitiessupporting
confidence: 85%
“…ascidian species with a short-lived larval stage or intertidal algae with limited dispersal ranges) in open and continuous marine systems, compared to mobile organisms (Soininen et al 2007, Tsujino et al 2010. Furthermore, smaller organisms, which respond more intensively to fine scale environmental variation due to their shorter generation times, may have lower similarity at small distances (Gillooly et al 2002, Tsujino et al 2010.…”
Section: Patterns Of Spatial Variation In Biofouling Communitiesmentioning
confidence: 99%
“…Nakaoka et al, 2005;Tsujino et al, 2009;Okuda et al, 2010). Numerous empirical studies have shown that the dispersal of many macroinvertebrate species and convergence of the variation of community structure (as well as functional diversity) are at the meso-scale level (i.e., tens of kilometers; Hovel, 2003;Boström et al, 2006;Reed and Hovel, 2006;Yamada et al, 2011).…”
Section: Study Areamentioning
confidence: 99%
“…This pattern can result from a variety of mechanisms, including environmental heterogeneity, dispersal limitation, migration, and stochastic events (Hubbell 2001, Hanson et al 2012. The effects of these mechanisms depend on the spatial scale over which they occur, and such scaledependent patterns have been observed for a variety of taxa in many environments; e.g., plant communities (Nekola andWhite 1999, Condit et al 2002), sessile invertebrate and algal communities (Tsujino et al 2009), and microbial communities (Ramette andTiedje 2007, Martiny et al 2011).…”
Section: Introductionmentioning
confidence: 99%